2010
DOI: 10.1002/cssc.200900255
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Generation by Photosystem II Core Complexes Tethered to Gold Surfaces

Abstract: By using a nondestructive, ultrasensitive, fluorescence kinetic technique, we measure in situ the photochemical energy conversion efficiency and electron transfer kinetics on the acceptor side of histidine-tagged photosystem II core complexes tethered to gold surfaces. Atomic force microscopy images coupled with Rutherford backscattering spectroscopy measurements further allow us to assess the quality, number of layers, and surface density of the reaction center films. Based on these measurements, we calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 26 publications
(30 reference statements)
2
25
0
Order By: Relevance
“…[32] To harvest light energy, it is thermodynamically beneficial to collect electrons when the photosynthetic component is in its high-energy state, such as photoinduced PS II. [33,34] Furthermore, it is advantageous to use a photosynthetic system that is able to use water as the electron donor such as PS II instead of PS I, in which an additional electron donor is required. Attempts have been made to immobilize the PS II reaction center on the electrode surface through cytochromes [25] and nickel nitrilotriacetic acid [35] as cross linkers.…”
Section: Introductionmentioning
confidence: 99%
“…[32] To harvest light energy, it is thermodynamically beneficial to collect electrons when the photosynthetic component is in its high-energy state, such as photoinduced PS II. [33,34] Furthermore, it is advantageous to use a photosynthetic system that is able to use water as the electron donor such as PS II instead of PS I, in which an additional electron donor is required. Attempts have been made to immobilize the PS II reaction center on the electrode surface through cytochromes [25] and nickel nitrilotriacetic acid [35] as cross linkers.…”
Section: Introductionmentioning
confidence: 99%
“…Technical applications are increasingly exploiting the efficiency of photosynthesis for solid-state devices mimicking photovoltaic cells. Photo-electric currents have been achieved with immobilized chloroplasts [7], thylakoid membranes [8-10], PSII [11, 12] or PSI [13-16] core complexes and isolated reaction centres [17-19]. One of the most promising current bio-photovoltaic without using elaborate or expensive surface chemistries is a PSI complex attached to a semiconductor, achieving a photocurrent density of 362 µA/cm 2 and 0.5 V [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, while the photochemical energy conversion efficiency of the freshly isolated PS2 was 0.7, the same parameter for the PS2 immobilized on Au was 0.53. This clearly indicated that the PS2 complexes were photochemically stable even after immobilization, but long-term stability was not discussed by the authors (Vittadello et al, 2010).…”
Section: Photosystem II As Photobiocatalystmentioning
confidence: 81%
“…To achieve that, Vittadello et al (2010) reported the application of histidine-tagged protein complex of PS2 from S. elongatus covalently bound to a gold electrode treated with Ni(2+)-nitrilotriacetic acid (Ni-NTA). The current density of the resulting photobioelectrochemical cell reached 43 mkA/cm 2 .…”
Section: Photosystem II As Photobiocatalystmentioning
confidence: 99%